Effects of strength training on bioenergetics parameters determined at velocity corresponding to maximal oxygen uptake in endurance runners - Damasceno, M.; Pasqua, L.; Gáspari, A.; Araújo, G.; de-Oliveira, F.; Lima-Silva, A.; Bertuzzi, R. (Science & Sports, 2018)
Objectives: The present study analyzes the impact of a strength training program on bioenergetics parameters determined at velocity corresponding to maximal oxygen uptake (vV'O2max). Methods: Sixteen recreational long-distance runners were divided into strength training (STG, n=9) and control (CG, n=7) groups. Before and after 8 weeks, the volunteers performed: maximal incremental treadmill test, constant-speed running at pre-training vV'O2max, and maximum dynamic strength test (1RM). Energy cost of running (ECr), and aerobic (AMET) and anaerobic (ANMET) metabolism contributions were estimated at vV'O2max. Results: No differences were observed at baseline between groups (P>0.05). After experimental period, there was an increase in 1RM for STG (27±18%, P=0.008), but not for CG (P>0.05). The changes in ECr (pre=0.254±0.038 vs. post=0.255±0.037kJ·m-1), AMET (pre=191.5±26.2 vs. post=193.0±31.7kJ), and ANMET (pre=20.9±6.4 vs. post=21.0±5.7kJ) were not significant different (P>0.05) to STG; as well as to CG (ECr - pre=0.260±0.046 vs. post=0.259±0.034kJ·m-1, AMET - pre=209.7±30.2 vs. post=203.3±26.6kJ, and ANMET - pre=19.3±6.4 vs. post=23.9±4.6kJ). Conclusions: These findings suggest that 8 weeks strength training improved the maximum dynamic strength and did not alter bioenergetics parameters measured at vV'O2max in recreational endurance runners.